Spiritual Health and Physical Activity Among Iranian Pregnant Women - Rabiepoor, Soheila (Journal of religion and health, 2019)
This study was aimed to investigate the relationship between spiritual health and physical activity among Iranian pregnant women during 2015. A cross-sectional descriptive-analytic design was adopted. A total number of 411 participants were selected by convenience sampling from Iranian women who regularly attended health centers for prenatal care. Data were collected using demographic questionnaire and Health-Promoting Lifestyle Profile questionnaire, 2nd edition. (Spiritual health and physical activity are two components of health-promoting lifestyle.) The data were analyzed, using descriptive statistics, t test, one-way ANOVA, Pearson's correlation coefficient, and regression. p values <0.05 were considered significant. The mean age of pregnant women was 27.90 ± 6.03 years. Spiritual health had the highest score (25.86 ± 4.7) and physical activity had the lowest score (11.31 ± 3.27), among six Health-Promoting Lifestyle Profile subscales. In fact, there was a statistically significant correlation between spiritual health and physical activity (p = 0.000). According to results, pregnant women have higher spiritual health and lower physical activity scores. There was a statistically significant correlation between spiritual health and physical activity. The findings of this study can be used in prenatal care, midwifery education, and maternal health policies.